Analisis Fundamental Saham Saat dan Setelah Covid-19 Pada PT Jasa Marga Tbk - Hanifah Restu Putri; Yenni Samri Juliati Nasution (Universitas Kristen Indonesia Toraja, 2024)
This research is based on the impact of the Covid-19 pandemic by looking at the ratio in the first year and the second year this pandemic hit, namely in 2020 and 2021. In the first year Covid-19 spread and paralyzed all crowd and face-to-face access, making toll roads even worse. little to use, after that in 2021, to be precise in the second year, the new normal edition was carried out to start improving life as before. This research is data-based or quantitative which shows results in the form of ratios. The ratios obtained are based on fundamental analysis using profitability ratios, namely ROA, ROE, PER and EPS with each existing formula. The ratios obtained in this research show that PT Jasa Marga Tbk has survived in the second year of the new normal era and achieved three ratios that increased from the previous year, even though in the first year the pandemic was affected by Covid-19.